RATIONAL SUFISM OF HARUN NASUTION: Phenomenological Historical Approach to His Thought and Intellectual Influence - Piet Hizbullah Khaidir; Abdul Kadir Riyadi; Idri idri; Azhar Ibrahim; Fathurrofiq Fathurrofiq (ULUL ALBAB Jurnal Studi Islam, 2023)
Sufism is a spiritual exercise dimension that is often done irationally in one hand. On the other hand, rationalism is a faculty of mind based totally on rational dimension. So, in fact, it is almost impossible to elaborate both of them in one bowl of life. However, Harun Nasution’s (HN) thought had blended both of them become a couple of wings to envision Indonesian muslim way of thinking and to aggregate his life both spiritually and ascetically.  The root of his thought genealogically can be traced in four steps. Firstly, HN’s literate religious family nurtured his childhood. Secondly, his further adventure dealing with rationalism idea surely affected his progressive thought. His work: The Place of Reason in Abduh’s Theology, Its Impact on His Theological System and Views articulates his strong point on rationalism in Islamic studies. Moreover, it became direct correction to school of Ash’aria theology. Thirdly, sufism aspect of  HN demonstrated himself as a consistent figure who do spiritual exercise (riyadhoh) for himself by enriching zikr and praying. Finally, his rational Islamic thought has influenced the Indonesian Islamic thought constellation within Indonesia muslim scholars until recently. In spite of many critics addressed to him, many appreciations also come to him. To analyze his faculty of thought, this paper aims at exploring datas on him based on historical phenomenological theory. It is to constitute the presence of subject (HN) in his historical life. His intentional consciousness with regards to his Islamic rationalism and sufism is a factor for rational sufism in the line of Indonesia’s Islamic thought constellation.